Estimation of successive coseismic vertical offsets using coeval sedimentary events - application to the southwestern limit of the Sea of Marmara's Central Basin (North Anatolian Fault) - Beck, C.; Campos, C.; Eris, K. K.; Cagatay, N.; de Lepinay, B. Mercier; Jouanne, F. (Copernicus Gesellschaft Mbh, 2015)
In the deep part of the Sea of Marmara (Turkey), the sedimentation developing upon the North Anatolian Fault is strongly influenced by the associated seismic activity, through gravity reworking (fluidized landslides) and tsunamis. Specific layers (homogenites + turbidites, HmTu), representing individual sedimentary events, have been characterized along three giant piston cores retrieved from the Cinarcik and Central (or Orta) basins. Pre-Holocene, nonmarine sediments, were analyzed, representing the last 1217 kyr BP (before present). For a 2 kyr long interval, 11 events could be precisely correlated on both sides of the Central Basin's southwestern scarp. For each of them, based on the specific depositional process, the thickness difference between the two sites was considered as a direct estimation of the vertical component of a coeval coseismic offset. The homogenite (upper) component accounts for the major part of the thickness difference (ranging from 36 to 144 cm). These offsets were considered as likely representing dominantly vertical throws, along the transtensional southwestern boundary of the inner, pull-apart Central Basin. In terms of natural hazards, further investigations on this local behavior should rather be directed to tsunami genesis.
Keywords: Late-Pleistocene; Transform Basin; Cinarcik Basin; Merida Andes; Pull-Apart; Earthquake; Turkey; Slip; Rupture; Record